DeLone & McLean Model and Expectation Confirmation Model in Improving the Role of Digital Product Innovation in the Banking Industry: Evidence from Sharia Banking Aceh Province - Ahlul Aqdi; Yusmita, Fifi (The International Journal of Financial Systems, 2024)
The three-day disruption of BSI Mobile due to a cyber-attack raised serious data security concerns, especially in Aceh, which relies heavily on Indonesia's largest Islamic banking system due to Qanun No. 11 on Islamic Financial Institutions. This study examines the effects of system quality, information quality, service quality, security, and price value on user satisfaction with mobile banking in Aceh, and its influence on continued usage intention. SEM-PLS analysis of 582 BSI customers and a review of 30 articles shows that service quality, security, and price value significantly enhance satisfaction, driving continued usage, while system and information quality do not.